Fatal Outcome of Membranoproliferative Glomerulonephritis in a Patient With Hidden Visceral Leishmaniasis - Ali Mansoursamaei; Maryam Valikhani; Hoofar Rafiee (Case Reports in Infectious Diseases)
Conclusion: This case underscores the importance of considering VL in the differential diagnosis of unexplained renal dysfunction, even in the absence of classic symptoms and in nonendemic regions. It highlights the potential for VL to present with atypical renal manifestations such as MPGN, leading to severe and irreversible renal damage if diagnosis and treatment are delayed. Early recognition and intervention are critical to improving outcomes in VL-associated renal disease.